Romania : 2016 Article IV Consultation-Press Release; Staff Report; Informational Annex; and Statement by the Executive Director for Romania. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses recent economic developments, outlook, and risks related to the Romanian economy. Romania made important progress in addressing economic imbalances and restoring growth after the global financial crisis. Prudent policies, partly in the context of successive IMF-supported programs, reduced vulnerabilities, and the fiscal and current account deficits improved markedly. However, economic policies have weakened recently and hard-won gains are at risk of being reversed. Governance problems have received more attention recently, and Romania has made progress compared to its peers in the fight against corruption. Staff's baseline projection is for growth to remain above potential in 2016-17.